2002
DOI: 10.1139/x02-002
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among northern flying squirrels, truffles, and microhabitat structure in Sierra Nevada old-growth habitat

Abstract: During 1997-1998, we investigated the influence of both the relative abundance of truffles, preferred food items, and microhabitat structure on the occurrence of northern flying squirrels (Glaucomys sabrinus Shaw) in old-growth forest habitat of the Sierra Nevada Range, U.S.A. Following live-trapping sessions, we searched the forest floor for truffle diggings and sampled the soil for truffles. Diggings were more abundant where flying squirrels were captured, suggesting squirrels were active near areas of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 51 publications
(80 reference statements)
4
50
0
Order By: Relevance
“…The unimodal (Gaussian) effect of shrub cover on G. sabrinus abundance (Fig. 5b) indicated that this species may require sufficient understory cover for foraging or concealment from predators (Pyare and Longland 2002). However, excessive shrub or understory cover may be negatively associated with G. sabrinus (Manning et al 2012) and may impede mobility of this volant species during foraging or predator evasion (Hackett and Pagels 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unimodal (Gaussian) effect of shrub cover on G. sabrinus abundance (Fig. 5b) indicated that this species may require sufficient understory cover for foraging or concealment from predators (Pyare and Longland 2002). However, excessive shrub or understory cover may be negatively associated with G. sabrinus (Manning et al 2012) and may impede mobility of this volant species during foraging or predator evasion (Hackett and Pagels 2003).…”
Section: Discussionmentioning
confidence: 99%
“…G. sabrinus forages extensively on truffles (fruiting bodies of hypogeous fungi- Waters and Zabel 1995), and the abundance, biomass, and frequency of truffles are significantly lower in recently burned than unburned stands in Sierra Nevada frequent-fire forests (Meyer et al 2005(Meyer et al , 2008. Elsewhere on the western slope of the Sierra Nevada, capture rates for G. sabrinus were consistently higher in forest patches with high canopy closure (≥ 75%- Waters and Zabel 1995;Meyer et al 2007a), adequate litter depth (≥ 2 cm- Meyer et al 2007a), and availability of truffles (Pyare and Longland 2002). Fires that burn large patches with sufficient intensity to remove overstory canopy or litter below a threshold suitable for foraging movements (< 55% canopy cover- Lehmkuhl et al 2006) and truffle production (≤ 3 cmMeyer et al 2008) may reduce habitat suitability for G. sabrinus.…”
Section: Discussionmentioning
confidence: 99%
“…The model from Program Presence also supports this claim with a 0.20 detection probability and a 0.63 occupancy estimate of the high boxes versus a 0.12 detection probability and a 0.29 occupancy estimate for low boxes. Flying squirrels may prefer higher boxes because higher canopy height might enhance gliding time and provide greater protective cover (Pyare and Longland, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly insignificant site-specific trends were noted for squirrel occupancy in 77% high versus 23% low nest boxes, suggesting preference for higher canopy refuges at all sites. Pyare and Longland (2002) found that there are two important factors affecting the nest site selection among tree squirrels: 1) mean distance to the nearest neighbor tree, and 2) mean percentage of canopy cover. These same researchers reported that flying squirrels were capable of gliding more than 50m from the higher canopy, in part because shorter gliding distances to lessen predation risk were preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Some EM mushrooms with expanding ranges are estimated to migrate less than 10 km per year (Pringle et al 2009), roughly in line with the 2 km per year rate estimated for invasive plants (Williamson et al 2005); this may imply that the migration capacity of most EM fungi is roughly equivalent to that of their tree hosts. Even hypogeous (underground) symbionts important to wildlife, such as truffles (Pyare and Longland 2002), may have some capacity to respond to climate change by undergoing fairly rapid range shifts (Büntgen et al 2011). The history of long-distance tree migrations, however, has shown that there is often a need for the right mycorrhizal species to be present when trees are translocated to distant habitat; trees lacking appropriate mycorrhizal partners may show poor productivity (Björkman 1970).…”
Section: Tree-associated Speciesmentioning
confidence: 99%